MODERNIST ELEMENTS, THEMES, AND REFLECTIONS IN THE SELECTED POEMS FROM A DRIFTING BOAT: AN ANTHOLOGY OF CHINESE ZEN POETRY - Ledesma, Jan Raen Carlo Mijaro; Manalastas, Aldrin Enciso; Manalastas, Katya Enciso (Sanata Dharma University, 2025)
This paper is an attempt to examine the modernist poetic and aesthetic purviews of selected poems from the anthology “A Drifting Boat: An Anthology of Chinese Zen Poetry.” In the regimes created by the poems, we recognize a literariness racked by internal and external contradictions. Hence, the analysis of the transitions and shifts is to be correlated with a modest chronicling of the past to show how their very bearings on the literary schemata of the works result to the formation of their modernist axioms and dictums. The paper presents the image of literature in the pace of change affirming the idea that the repercussions brought by the wars and westernization are the forces that have completely devalued traditional Chinese society and its various conservative characteristics. Using the descriptive-analytical design, the poems disclosed modernist issues, themes and philosophies verging on individualism, experimentation (breaking the conventional practices in literature), sense of loss and exile and nostalgia, narrative authority as a reflection of the multiplicities of truth and diversification of realities, fragmentation and destruction effected by the arrival of the Western powers in their society, and the occurrence of the states of absurdism and existentialism brought by the rush of daily life.